2012
DOI: 10.1007/s10722-012-9831-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis with SNPs from BOPA1 shows clearly defined groupings of Western Mediterranean, Ethiopian, and Fertile Crescent barleys

Abstract: The discovery of Hordeum spontaneum C. Koch, a wild ancestor of cultivated barley, in Morocco in 1978 led to the proposal of a multicentric origin for this crop, as an alternative to the widely accepted theory of a single centre of domestication in the Fertile Crescent. Since this discovery, we have tested this hypothesis using the most advanced genetic techniques available at the time, from CM-proteins to RFLP and DNA-chloroplast markers. Nowadays, the availability of single nucleotide polymorphism (SNP) mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Subpopulation 5, which consisted primarily of Eritrean and Ethiopian landraces, was quite distinct from other African and Asian accessions and included both two-row and six-row types and an intermediate type of labile barley, exclusive to this part of Africa, whose main feature is a different number of grains at each rachis node [54], [55]. The genetic distinctiveness of barley germplasm from the Horn of Africa has been reported previously [56], [57]. Some accessions from Morocco and all the accessions from Bolivia were included in subpopulation 5.…”
Section: Discussionmentioning
confidence: 92%
“…Subpopulation 5, which consisted primarily of Eritrean and Ethiopian landraces, was quite distinct from other African and Asian accessions and included both two-row and six-row types and an intermediate type of labile barley, exclusive to this part of Africa, whose main feature is a different number of grains at each rachis node [54], [55]. The genetic distinctiveness of barley germplasm from the Horn of Africa has been reported previously [56], [57]. Some accessions from Morocco and all the accessions from Bolivia were included in subpopulation 5.…”
Section: Discussionmentioning
confidence: 92%
“…The evaluation of both SBCC parents revealed that they present a virulence pattern close to the resistance traditionally described as Rh4 (Graner and Tekauz 1996), later renamed by Bjørnstad et al (2002) as Rrs1 Rh4 , to indicate that it belongs to the Rrs1 locus. This resistance seems typical of accessions originating in North Africa or the Western Mediterranean region: CIho 3515 is Spanish, Osiris and Malebo (parent of Yerong) from Algeria and La Mesita is from Egypt, along one of the possible paths of expansion of barley from the Fertile Crescent towards the West (Baba et al, 2011;Igartua et al 2013). Therefore, it may have evolved in response to pathotypes prevalent in that region.…”
Section: Discussionmentioning
confidence: 96%
“…More recent studies confirmed the uniqueness of Ethiopian landraces in varying degrees (Alamerew et al ., ; Haile et al ., ; Teklu et al ., ), although using smaller panels and reduced genotyping density. This degree of differentiation seems to be a common feature of Ethiopian crops and is reported on barley as well (Igartua et al ., ). The most significant PC in our PCA clearly separates improved wheat lines and Mediterranean material from landraces (Figure a).…”
Section: Discussionmentioning
confidence: 97%